The Concept of Educating Righteous Children from the Perspectives of Shaykh At-Tihami and Shaykh Nawawi al- Bantani: Relevance to Islamic Education in Indonesia - Miftahus Surur (IERA, Islamic Education and Research Academy, 2025)
This study, entitled “The Concept of Educating Righteous Children from the Perspectives of Shaykh At-Tihami and Shaykh Nawawi al-Bantani: Relevance to Islamic Education in Indonesia”, aims to describe the scholars’ concepts of child education, the strategic role of parents, and the relevance of their ideas to current Islamic education in Indonesia. Using a qualitative approach with a library research method, data were obtained from Qurratul ‘Uyun by Shaykh Muhammad At-Tihami and Uqud al-Lujain by Shaykh Nawawi al-Bantani, supported by relevant literature. Descriptive-comparative analysis identified similarities and differences in their perspectives. Shaykh At-Tihami emphasizes education before birth, including spouse selection and marital etiquette, while Shaykh Nawawi focuses on parental responsibility in instilling Islamic values and exemplary conduct. Both agree that family is the foundation of moral and spiritual education, and their ideas remain relevant to Indonesia’s Islamic education, which places the family as the primary environment for nurturing faith and character.